(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Various weight % of Gadolinium doped ZnO nanocrystals were prepared by using simple co-precipitation method. All the prepared Gd doped ZnO nanocrystals are annealed at 450°C. The synthesized nanocrystals are characterized by using various techniques like X-ray diffraction, scanning electron microscope and UV-Vis spectroscopy. The influence of various weight % of Gadolinium doping on structural, optical and photo-catalytic performance of the ZnO nanocrystals has been investigated. Photo-catalytic decolourization was analysed for Gadolinium doped ZnO nanocrystals by using Methylene blue as model dye. It has been found that 0.075% Gd doped ZnO nanocrystals shows enhanced catalytic performance.